2014
DOI: 10.1371/journal.pone.0092171
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Eotaxin and MCP-1 in Juvenile Dermatomyositis Median 16.8 Years after Disease Onset; Associations with Disease Activity, Duration and Organ Damage

Abstract: ObjectiveTo compare cytokine profiles in patients with juvenile dermatomyositis (JDM) after medium to long-term follow-up with matched controls, and to examine associations between cytokine levels and disease activity, disease duration and organ damage.MethodsFifty-four JDM patients were examined median 16.8 years (2–38) after disease onset (follow-up) and compared with 54 sex- and age-matched controls. Cytokine concentrations in serum were quantified by Luminex technology. In patients, disease activity score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 35 publications
(46 reference statements)
5
22
1
Order By: Relevance
“…A recent study using the SOMAscan assay also identified both galectin-9 and CXCL10 among the top up-regulated proteins in juvenile DM, correlating with disease activity as assessed by the PhGA (53). CXCL10 levels were previously shown to correlate with disease activity in juvenile DM (26,(30)(31)(32)54), and CXCL10 is well known to be an interferon-inducible chemokine that can be elevated in other types of myositis and autoimmune diseases (29,33). In our study, galectin-9 was a specific biomarker for inflammatory myopathies.…”
Section: Discussionsupporting
confidence: 65%
“…A recent study using the SOMAscan assay also identified both galectin-9 and CXCL10 among the top up-regulated proteins in juvenile DM, correlating with disease activity as assessed by the PhGA (53). CXCL10 levels were previously shown to correlate with disease activity in juvenile DM (26,(30)(31)(32)54), and CXCL10 is well known to be an interferon-inducible chemokine that can be elevated in other types of myositis and autoimmune diseases (29,33). In our study, galectin-9 was a specific biomarker for inflammatory myopathies.…”
Section: Discussionsupporting
confidence: 65%
“…MRI detected muscle damage (such as muscle atrophy and fatty infiltration) was found in approximately 50% of patients. The serum cytokine eotaxin and the serum myokines MCP-1 and IP-10 were elevated in patients compared to controls (77). MCP-1 was also elevated in patients with active disease compared to respective controls, and correlated with disease damage in the whole patient group.…”
Section: Organ Specific Long-term Outcomesmentioning
confidence: 84%
“…The innate immune system also appears to play a role in JDM. Plasmacytoid dendritic cells and macrophage-secreted proteins are present in inflamed JDM patient muscles (12,13), and chemokines eotaxin, monocyte chemoattractant protein-1, and IFN-γ-induced protein 10 are elevated in JDM patient serum in comparison with healthy controls (14). In addition, specific TNF and IL-1 alleles as well as a type I IFN-stimulated gene signature are associated with JDM disease risk (15,16).…”
Section: Introductionmentioning
confidence: 99%